2018
DOI: 10.33086/jhs.v11i2.110
|View full text |Cite
|
Sign up to set email alerts
|

Penundaan Penjepitan Tali Pusat Terhadap Kadar Bilirubin Bayi Baru Lahir

Abstract: Delayed cord clamping can have an effect on the hematological value of the newborn. The advantages of cord clamping delays include preventing anemia, increasing hematocrit levels, reducing postpartum incidence, optimizing oxygen transfusion to the baby, improving maternal and infant closeness and promoting infant brain growth. The disadvantage of cord clamping delays is the occurrence of hyperbilirubin and policitemia in newborns. The purpose of this study was to identify the levels of bilirubin newborns. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…However, many studies have found that delaying clamping and cutting the umbilical cord has proven to have many benefits including preventing anemia, increasing hematocrit levels, reducing the incidence of postpartum hemorrhage, optimizing oxygen transfer to the baby, increasing the closeness of mother and baby and increasing the growth of the baby's brain 3 . Other benefits include BBL bilirubin levels 4 , and neurodevelopment 5 .…”
Section: Worldmentioning
confidence: 99%
“…However, many studies have found that delaying clamping and cutting the umbilical cord has proven to have many benefits including preventing anemia, increasing hematocrit levels, reducing the incidence of postpartum hemorrhage, optimizing oxygen transfer to the baby, increasing the closeness of mother and baby and increasing the growth of the baby's brain 3 . Other benefits include BBL bilirubin levels 4 , and neurodevelopment 5 .…”
Section: Worldmentioning
confidence: 99%
“…Banyak manfaat yang didapatkan ketika dilakukan penundaan pemotongan tali pusat diantaranya adalah mencegah anemia, meningkatkan kadar hematokrit, mengurangi kejadian perdarahan postpartum, mengoptimalkan trasfusi oksigen ke bayi, meningkatkan kedekatan ibu dan bayi serta meningkatkan pertumbuhan otak bayi (Astuti, et al, 2018). Ketika penjepitan tali pusat ditunda, bayi memiliki kadar hemoglobin yang lebih tinggi antara satu dan dua hari setelah lahir dan lebih kecil kemungkinannya untuk kekurangan zat besi tiga sampai enam bulan setelah lahir.…”
Section: Pendahuluanunclassified
“…Sedangkan Materniti (2018) mengungkapkan bahwa kadar hemoglobin pada rata-rata bayi yang dilakukan penjepitan dan pemotongan tali pusat segera, yaitu tepatnya pada 30-60 detik setelah lahir didapatkan rata-rata kadar Hb sebesar 15,88 gr/dL. 12 Hal tersebut membuktikan bahwa bayi yang menerima intervensi pemerahan tali pusat memiliki kadar hemoglobin lebih tinggi jika dibandingkan dengan ratarata bayi yang tidak dilakukan pemerahan tali pusat.…”
Section: Pembahasanunclassified